Exploration of preschool teachers’ views towards vak’s learning style in pre-number skills - Idris, Julianty; Jamil, Norly (Southeast Asia Early Childhood Journal, 2025)
This study explores preschool teachers’ perspectives on their knowledge, awareness, and interest in Visual, Auditory, and Kinesthetic (VAK) learning styles within the context of teaching pre-number skills. This study uses a qualitative approach, by involving a total of 6 preschool teachers from Melaka to be interviewed to obtain an in-depth perspective on the understanding and implementation of the VAK learning style in teaching pre-number skills. Regarding knowledge, the findings indicate that three teachers are knowledgeable about VAK learning styles, two teachers understood and recognized the importance of VAK only after the researcher’s explanation, and one teacher had merely heard of VAK without implementing it in teaching. In terms of awareness, all teachers acknowledged the importance of the VAK approach after receiving an explanation and expressed that this approach could help students better understand pre-number skills. Concerning interest, all teachers indicated that the VAK approach could engage students and assist teachers in achieving their teaching objectives. This study’s primary contribution is discovering that explanations and guidance on VAK learning styles can enhance teachers’ awareness and understanding and their interest in applying it in teaching pre-number skills. The study’s implications suggest that continuous training and guidance on VAK learning styles should be provided to preschool teachers to enrich the teaching and learning of pre-number skills. Future research is recommended to investigate the long-term effects of using VAK learning styles on the cognitive development of preschool students. With increased knowledge and awareness, it is hoped that preschool teachers can leverage VAK learning styles to enrich children’s learning experiences and pre-number skills.